Surface modification of electrospun fibres for biomedical applications: A focus on radical polymerization methods. (November 2016) - Duque Sánchez, Lina; Brack, Narelle; Postma, Almar; Pigram, Paul J.; Meagher, Laurence
Abstract: The development of electrospun ultrafine fibres from biodegradable and biocompatible polymers has created exciting opportunities for biomedical applications. Fibre meshes with high surface area, suitable porosity and stiffness have been produced. Despite desirable structural and topographical properties, for most synthetic and some naturally occurring materials, the nature of the fibre surface chemistry has inhibited development. Hydrophobicity, undesirable non-specific protein adsorption and bacterial attachment and growth, coupled with a lack of surface functionality in many cases and an incomplete understanding of the myriad of interactions between cells and extracellular matrix (ECM) proteins have impeded the application of these systems. Chemical and physical treatments have been applied in order to modify or control the surface properties of electrospun fibres, with some success. Chemical modification using controlled radical polymerization, referred to here as reversible-deactivation radical polymerization (RDRP), has successfully introduced advanced surface functionality in some fibre systems. Atom transfer radical polymerization (ATRP) and reversible addition fragmentation chain transfer (RAFT) are the most widely investigated techniques. This review analyses the practical applications of electrospinning for the fabrication of high quality ultrafine fibres and evaluates the techniques available for the surface modification of electrospun ultrafine fibres and includes a detailed focus on RDRP approaches.